PERBANDINGAN PELAKSANAAN FUNGSI LEGISLASI ANTARA DEWAN PERWAKILAN RAKYAT DI INDONESIA DAN REPRESENTATIVES DI URUGUAY: Comparison of the Legislative Functions between the House of Representatives in Indonesia and the Representatives in Uruguay - Amirul Huda Musyafa Samudra; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2024)
A democratic state is characterized by the sovereignty of the people, where the highest power lies with the citizens. One manifestation of this sovereignty is the role of representative bodies in the legislative process. This study examines the role of the Indonesian House of Representatives and the Representatives in Uruguay in the law-making process, and evaluates their legislative performance. The research employs normative legal methodology, with descriptive writing, and uses secondary data. The result and Conclusions are drawn using deductive logic. The study finds that the Indonesian House of Representatives has a national legislative program that includes draft laws, while the Representatives in Uruguay do not have such a program. In Indonesia, 24 out of 247 draft laws in the 2020-2024 period were successfully enacted, whereas in Uruguay, 412 draft laws were passed into law during the same period.